2019
DOI: 10.1038/s41598-019-50888-5
|View full text |Cite
|
Sign up to set email alerts
|

The adequacy of tissue microarrays in the assessment of inter- and intra-tumoural heterogeneity of infiltrating lymphocyte burden in leiomyosarcoma

Abstract: The characterisation and clinical relevance of tumour-infiltrating lymphocytes (TILs) in leiomyosarcoma (LMS), a subtype of soft tissue sarcoma that exhibits histological heterogeneity, is not established. The use of tissue microarrays (TMA) in studies that profile TIL burden is attractive but given the potential for intra-tumoural heterogeneity to introduce sampling errors, the adequacy of this approach is undetermined. In this study, we assessed the histological inter- and intra-tumoural heterogeneity in TIL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Previous studies involved TILs and its subtypes also correlated with survival in soft tissue sarcoma [ 39 41 ]. A study involved 47 leiomyosarcomas revealed an average number of 10.5 CD4+ TILs and 16.1 CD8+ TILs per high power filed (CD4 33.87/mm 2 , CD8 51.93/mm 2 ) [ 42 ], which is lower than the average number in MBC with mesenchymal elements (CD4 209.99 ± 140.10/mm 2 , CD8 83.34 ± 78.09/mm 2 ). Further, no significant difference in TILs was found among different mesenchymal subtypes ( p = 0.30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies involved TILs and its subtypes also correlated with survival in soft tissue sarcoma [ 39 41 ]. A study involved 47 leiomyosarcomas revealed an average number of 10.5 CD4+ TILs and 16.1 CD8+ TILs per high power filed (CD4 33.87/mm 2 , CD8 51.93/mm 2 ) [ 42 ], which is lower than the average number in MBC with mesenchymal elements (CD4 209.99 ± 140.10/mm 2 , CD8 83.34 ± 78.09/mm 2 ). Further, no significant difference in TILs was found among different mesenchymal subtypes ( p = 0.30).…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve comparable results and validate these markers, we suggest a standardised, international consensus for the investigation and validation of prognostic biomarkers in PDAC is developed. In line with other cancers, optimal sampling protocols for TMA analysis of PDAC are required to mitigate the effects of morphomolecular heterogeneity [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of transcriptomic signatures in sarcoma have been developed from bulk measurements of tumour specimens. However, all the studies described to date have not systematically established if the performance of these prognostic signatures are influenced by the intratumoural heterogeneity inherent within STS 15 , 74 , for instance by evaluation of distinct heterogeneous tumour regions with spatial transcriptomics. Furthermore, there is a diversity of distinct cell types in the tumour microenvironment (e.g., immune cells, fibroblasts and endothelial cells) which can be readily assessed by histopathology review but is lost in bulk transcriptomic data.…”
Section: Outstanding Questionsmentioning
confidence: 99%